2016
DOI: 10.1097/igc.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Gestational Trophoblastic Neoplasia: A 15-Year Hospital-Based Study

Abstract: In the past 15 years, the incidence of GTN was still higher than in other countries from 1994 to 2009, and the mean age of patients with GTN was increased significantly, especially for the patients older than 40 years. Furthermore, patients with no clinical manifestations increased significantly, which should be paid more attention in the future works. Serum level of beta human chorionic gonadotropin and pelvic ultrasonography are still 2 important indexes for diagnosing and monitoring condition of GTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Increase in maternal age, which is the most frequently cited risk factor, has a proportional effect on the incidence of post-molar GTN [ 3 , 4 ]. Tow, Savage and Tsukmoto et al [ 5 7 ] reported that women greater than 40 years old had a probability of 23-37% of developing persistent GTN after uterine evacuation, while the likelihood in women older than 50 years old was as high as 31-56%.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in maternal age, which is the most frequently cited risk factor, has a proportional effect on the incidence of post-molar GTN [ 3 , 4 ]. Tow, Savage and Tsukmoto et al [ 5 7 ] reported that women greater than 40 years old had a probability of 23-37% of developing persistent GTN after uterine evacuation, while the likelihood in women older than 50 years old was as high as 31-56%.…”
Section: Introductionmentioning
confidence: 99%
“…Since most studies on GTN are based on hospital studies with small samples, it is difficult to estimate their incidence. Compared with Western countries, the incidence of GTN is higher in Southeast Asia and Africa [ 21 , 22 ]. Our hospital is the GTN treatment center in Northwest China.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to non-standard treatment in primary hospitals, there are more cases of chemotherapy resistance. In our previous study, the incidence of invasive mole and CC decreased from 9.0 to 2.7 per 1000 deliveries in 15 years (from 1994 to 2009) [ 22 ]. Despite this continuous decrease, the number of these cases was still higher than in some developed countries [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal age of ≥40 years increases the HM risk to 5–10 times, 3 like the risk of GTN following abortion. 4 5 6 According to Savage, et al, 7 while the complete molar pregnancy rate at ages 14–40 years is <1/1000 pregnancies, the rate rises to about 1/156 pregnancies at age 45 and is very high in older women aged ≥50 years, at about 1/8 pregnancies. The rate of developing GTN after abortion also rises with age, specifically around 23%–37% in women aged ≥40 years, whilst it is very high in women >50 years at about 31%–56%.…”
Section: Introductionmentioning
confidence: 99%